(untitled) (Medico Legal Update, 2020)
Objectives: Hematological changes are among the most common complications encountered in malaria. This study analyzes and statistically evaluates the hematological changes as a diagnostic test for malaria in patient with acute febrile illness. Method: Hundred samples were diagnosed positive by the Leishman’s stained thick blood film. The data were collected from the central lab, Uttar Pradesh University of Medical Sciences, Saifai, Etawahduring May 2017 to August, 2019. Laboratory records of people suspected with malaria infection such as fever other signs and symptoms as medical doctor recommended were reviewed. Results: The finding showed that 100 patients were diagnosed to have malaria by positive smear report by microscopy. Of these were 4 were caused byP.falciparum, whereas 96 were caused by P.vivax . No patient with co-infection of P.falciparum and P.vivax were found. The following parameters were significantly lower in malaria- infected patients; red blood cells (RBCs) count, hemoglobin (Hb), platelets count, white blood cells (WBCs) counts, neutropil, monocyte, lymphocyte and eosinophil counts, while Mean corpuscular volume, Mean corpuscular hemoglobin, Mean corpuscular hemoglobin concentration, neutrophil-lymphocyte ratio (NLR) and monocyte-lymphocyte ratio (MLR) were higher in comparison to non- malaria infected patients. Thrombocytopenia was present in 91% of malaria infected patients. Conclusion: Patients infected with malaria exhibited important changes in most of hematological parameters with low hemoglobin, platelets, WBCs and lymphocyte counts being the most important predictors of malaria infection.